Early Near Eastern and South East European Gods - Makkay, János
A) Near Eastern Finds and Representations; 1) Small Figurines and Reliefs 2) Representations on Cylinder Seals; 3) The Development of Sickle-Swords from Sickles; B) The Sickle-Shaped Weapon in Mythology; 1) Near Eastern Data; 2) Parallels in Early Greek Mythology; C) The Neolithic God with the Sickle Attribute in South East Europe and its Ties to the Near East; D) The Religion of Late Neolithic South East Europe and that of Early Greece.